2017
DOI: 10.1007/s00011-017-1058-y
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast improves the changes of cytoskeletal and adaptor proteins of human podocytes by interleukin-13

Abstract: Our results suggest that targeting IL-13 may be one of the important cytokines in the pathogenesis of MCNS and targeting IL-13 could be one of the potential therapeutic strategies in MCNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…As most primary MCNS cases exhibit a high response rate to corticosteroids, its pathogenesis has been speculated to be immune-mediated, especially involving T cell-associated mechanisms [1,4]. Therefore, multiple studies have been conducted to explore the immunological basis of NS [5][6][7][8][9][10][11][12][13], and several studies specifically suggested T-helper 2 lymphocyte (Th2)dependency by demonstrating over-activity of type 2 helper T cells (Th2) and decreased Th1/Th2 ratios, thus highlighting Th2 predominance in NS [8,14,15]. Therefore, more studies have been performed with an aim to validate the role of Th2 cytokines such as interleukin (IL)-4, IL-5, and IL-13 in NS [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…As most primary MCNS cases exhibit a high response rate to corticosteroids, its pathogenesis has been speculated to be immune-mediated, especially involving T cell-associated mechanisms [1,4]. Therefore, multiple studies have been conducted to explore the immunological basis of NS [5][6][7][8][9][10][11][12][13], and several studies specifically suggested T-helper 2 lymphocyte (Th2)dependency by demonstrating over-activity of type 2 helper T cells (Th2) and decreased Th1/Th2 ratios, thus highlighting Th2 predominance in NS [8,14,15]. Therefore, more studies have been performed with an aim to validate the role of Th2 cytokines such as interleukin (IL)-4, IL-5, and IL-13 in NS [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Lai et al suggested that IL13 overexpression could lead to podocyte injury with downregulation of proteins such as nephrin, podocin, and dystroglycan and a concur rent upregulation of B71 in MCNS induced rat 17) . After that, our previous studies reported that IL13 was involved in the changes of ZO1 proteins in podocytes which could www.chikd.org be a pathogenesis of MCNS 14,18) . Other recent studies have shown that increase in IL13 production was to cause fre quent relapse in SSNS 13,19) .…”
Section: Discussionmentioning
confidence: 98%
“…We recently found pathological molecular changes in podocyte proteins by IL-13. We previously reported that IL-13 increased podocyte permeability through the modulation of ZO-1 110) , modulated the changes of cytoskeletal and adaptor proteins 111) , and increased podocyte apoptosis 112) , resulting in proteinuria and podocyte injury. However, the supposed role of circulating IL-13 in proteinuria in MCD patients is questionable because the elevated serum IL-13 levels were not found in MCD patients during relapse 66) and have been reported in patients with NS during remission compared with the controls 113) .…”
Section: Interleukin-13 (Il-13)mentioning
confidence: 99%